Dietary Inorganic Nitrate Protects Hepatic Ischemia-Reperfusion Injury Through NRF2-Mediated Antioxidative Stress - Li, Shaorong; Jin, Hua; Sun, Guangyong; Zhang, Chunmei; Wang, Jinsong; Xu, Hufeng; Zhang, Dong; Wang, Songlin (Frontiers in Pharmacology, 2021)
Abstract Objectives: Hepatic ischemia-reperfusion injury (HIRI) is of common occurrence during liver surgery and liver transplantation and may cause hepatic impairment, resulting in acute liver dysfunction. Nitrate plays an important physiological regulatory role in the human body. Whether dietary nitrate could prevent HIRI is, however, unknown. Methods: A HIRI mouse model was established that the blood supply to the median lobe and left lateral lobe was blocked for 60 minutes through the portal vein and related structures by an atraumatic clip. Sodium nitrate (4 mM) was administrated in advance through drinking water to compare the influence of sodium nitrate and normal water on HIRI. Results: Liver necrosis and injury aggravated after HIRI. The group treated with sodium nitrate showed the lowest activities of plasma aminotransferase and lactate dehydrogenase and improved outcomes in histological investigation and TUNEL assay. Mechanistically, sodium nitrate intake increased plasma and liver nitric oxide levels, upregulated nuclear factor erythroid 2-related factor 2 (NRF2)-related molecules to reduce malondialdehyde level and increase the activity of antioxidant enzymes to modulate hepatic oxidative stress. Conclusion: Dietary inorganic nitrate could prevent HIRI, possibly by activating the NRF2 pathway and modulating oxidative stress. Our study provides a novel therapeutic compound that could potentially prevent HIRI during liver transplantation or hepatic surgery.